ANALISIS INFORMASI FUNDAMENTAL RETURN SAHAM PADA PERUSAHAAN INDEKS LQ 45 DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Dewi Yulianti, 13.05.51.0197 (Students' Journal of Economic and Management, 2017)
The study aims to examine and analyze the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Total asset Turnover (TATO) and Return On Asset (ROA) to Stock Return of Companies Indeks LQ 45 that listed on Indonesian Stock Exchange on the period 2012-2015. The population in this study is a Companies Indeks LQ 45 that listed on Indonesian Stock Exchange from 2012 until 2015. But only meet the crieria are only samples. The samples are determined using purposive sampling technique. Data analysis was performed using panel data regression with selection between Pooled Least Square (PLS), Fixed Effect Model (FEM) and Random Effect Model (REM) through the Chow test and Hausman test. Hausman test result of this study recommends using REM. Based on the output REM showed that the CR has no effect on stock return. DER has a significant positive effect on stock return. TATO has a significant positive effect on stock return and ROA has a significant positive effect on stock return. The ability independent variable the explain of change of the variables return stock only 37,5% the rest was donated variables other than model. Then seen from constant value the greatest is in the Semen Indonesia and the smallest to the Bumi Serpong Damai. Keyword: Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return on Asset (ROA), Return Saham (RS)